Protocol for the Redefining Maternal Anemia in Pregnancy and Postpartum (ReMAPP) study: A multisite, international, population-based cohort study to establish global hemoglobin thresholds for maternal anemia. - Emily R Smith; Zahra Hoodbhoy; Aneeta Hotwani; Fyezah Jehan; Amna Khan; Imran Nisar; Nida Yazdani; Santosh Joseph Benjamin; Anne George Cherian; Venkata Raghava Mohan; Sunitha Varghese; Balakrishnan Vijayalekshmi; et al. (PLoS ONE)
Background Anemia affects one in three pregnant women worldwide, with the greatest burden in South Asia and sub-Saharan Africa. During pregnancy, anemia has been linked to an increased risk of adverse maternal and neonatal health outcomes. Despite widespread recognition that anemia can complicate pregnancy, critical gaps persist in our understanding of the specific causes of maternal anemia and the cutoffs used to diagnose anemia in each trimester and in the postpartum period. Methods and analysis The Redefining Maternal Anemia in Pregnancy and Postpartum (ReMAPP) study is a multisite, prospective, cohort study nested within the Pregnancy Risk, Infant Surveillance, and Measurement Alliance (PRISMA) Maternal and Newborn Health study. Research sites are located in Kenya, Ghana, Zambia, India, and Pakistan. Participants are up to 12,000 pregnant women who provide serial venous blood samples for hemoglobin assessment at five time points: at <20 weeks, 20 weeks, 28 weeks, and 36 weeks gestation and at six weeks postpartum. We will use two analytical approaches to estimate hemoglobin thresholds for defining anemia: (1) clinical decision limits for cutoffs in each trimester and at six weeks postpartum based on associations of hemoglobin levels with adverse maternal, fetal, and neonatal health outcomes and (2) reference limits for gestational-week-specific cutoffs and at six weeks postpartum for mild, moderate, and severe anemia based on tail statistical percentiles of hemoglobin values in a reference (i.e., clinically healthy) subpopulation. We will also conduct biomarker-intensive testing among a sub-sample of participants in each trimester to explore underlying contributing factors of maternal anemia. Ethics and dissemination The study received local and national ethical approvals from all participating institutions. Findings from multisite analyses will be published among open-access, peer-reviewed journals and disseminated with local, national, and international partners. Strengths and limitations Novel study design to allow multiple analytical approaches (clinical decision limits and reference limits) in the same population to establish hemoglobin thresholds.Use of gold standard methods and external quality assurance programs to ensure harmonized hemoglobin measurement across sites.Inclusion of biomarker-intensive study arm to examine the etiology of anemia among pregnant women.All data is contributed by populations historically underrepresented in research in low- and middle-income countries. Trials registration ClinicalTrials.gov (PRISMA-MNH 2022; NCT05904145).